Enhancing Elementary Students' 4C Communication Skills Through SAVI (Somatic, Auditory, Visual, Intellectual) Learning Model - Widyaningrum, Neni; Relmasira, Stefanus Christian (Papanda Publisher, 2025)
Contemporary elementary education faces significant challenges in developing students' 21st-century communication skills, particularly in mathematics learning contexts where traditional teacher-centered approaches often render students passive and hesitant to engage in meaningful discourse. The SAVI (Somatic, Auditory, Visual, Intellectual) learning model presents a promising multisensory approach that may address these communication skill deficiencies by engaging students holistically through diverse sensory modalities. This quasi-experimental study employed a pretest-posttest control group design involving 38 fourth-grade students at SD Negeri Gendongan 01 Salatiga, Indonesia. Participants were divided into experimental (n=19) and control (n=19) groups using purposive sampling. The experimental group received SAVI-based mathematics instruction focusing on pattern recognition, while the control group participated in conventional teaching methods. Data collection utilized validated communication skill assessment instruments, structured observations, and semi-structured interviews. Statistical analysis was conducted using SPSS version 25, employing independent samples t-tests to examine between-group differences. The experimental group demonstrated significantly superior communication skill achievement, with 42.11% of students reaching very high competency levels compared to 15.79% in the control group. Statistical analysis revealed significant differences between groups (p = 0.003 < 0.05, t = -3.126, df = 36), with a substantial mean difference of -19.342 points favoring the experimental group. The effect size indicated practically significant improvements in students' abilities to articulate mathematical reasoning, engage in collaborative problem-solving, and express creative solutions. These findings provide empirical validation that SAVI implementation significantly enhances elementary students' 4C communication competencies beyond conventional instructional approaches. The results support multisensory learning theories and suggest substantial implications for teacher preparation, curriculum development, and educational policy formulation in fostering 21st-century communication skills.